The motives of professional athletes to consume sustainable, plant-based food: Contribution of personal values, intrinsic-, and extrinsic motivations to food choices - Noponen, Petra (My University, 2021)
Professional athletes are expected to follow a strict diet with specific nutritional guidelines, and their food choices are typically formed to maximize their athletic performance. With the new era of sustainable eating, where plant-based food choices have become a norm for many consumers, athletes' have also gotten new complexities to consider while making their food choices. The aim of this research is to explore why professional athletes consume sustainable, plant-based food, by exploring the different values, food choice motives and intrinsic- and extrinsic motivations which reflect on athletes' motives to make sustainable food choices. Food choices are complex decisions, which include the decisions of when, what, with whom, and how to consume, and the decisions are influenced by the life course and previous experiences of consumers, as well as personal values and motivations. Consumers’ personal values, such as benevolence, universalism and stimulation, act as the abstract guidelines for consumers to make certain food choices. Besides, the food choice motives, including price, taste, convenience, and health, are considered as more practical motives that influence consumers’ food choices. However, with the consumer group of professional athletes, the intrinsic motivations that aim to maximize athletic performance, influences athletes’ food choices depending on their personal goals and timing of the season. In addition to intrinsic motivations, the extrinsic motivations also affect the athletes' food choices in certain situations. However, the external motivations are not based on the athlete's own motivation, and those often arise due to pressure, instructions, knowledge, or support from external sources of friends, family, or coaches. The research was conducted as qualitative research of semi-structured interviews, including professional athletes as study participants from different sports fields. The study's findings suggest that athletes are concerned about the health- and environmental factors that their diet and consumption patterns contribute to the outside world. The main motives that reflect on their food choices are taste, price, and convenience. Remarkably, the motive of convenience is particularly influential for athletes, which often leads professional athletes to favor food products that are easy and quick to prepare and fit well into their busy training schedules. Athletes would be motivated to make more sustainable food choices if it would positively contribute to their athletic performance, and if their friends or partners would also eat similarly. However, the lack of knowledge on sustainability matters acts as a barrier to make food choices that support both: sustainability of the earth and athletic performance, which could be an interesting topic for future research.

Ammattiurheilijoiden odotetaan syövän terveellistä ruokaa tarkan ruokavalion mukaisesti, ja heidän ruokavalintansa on tyypillisesti muodostettu tukemaan maksimaalista suorituskykyä. Kuitenkin, kestävästä syömisestä ja kasvipohjaisista ruokavalinnoista on tullut kuluttajien uusi normi, ja urheilijatkin ovat alkaneet pohtimaan uusia näkökulmia tekemässään ruokavalintoja, jotka ottavat huomioon ruoan kestävyyden, sekä urheilun suorituskyvyn maksimoinnin. Tämän tutkimuksen tarkoitus on tutkia ammattiurheilijoiden motiiveja syödä kestävää ruokaa, ja tutkia heidän arvojen, sekä sisäisten- ja ulkoisten motivaatiotekijöiden vaikutusta ammattiurheilijoiden kestäviin ja kasvipohjaisiin ruokavalintoihin. Urheilijoiden ruokavalinnat ovat monimutkaisia päätöksiä, joihin sisältyvä päätökset milloin, mitä, kenen kanssa ja miten kuluttajat syövät ruokaa. Lisäksi päätöksiin vaikuttavat urheilijoiden elämänkulku ja aiemmat kokemukset ruoasta, sekä henkilökohtaiset arvot ja motivaatiot. Kuluttajien henkilökohtaiset arvot, kuten hyväntahtoisuus, universalismi ja stimulaatio, toimivat abstrakteina ohjenuorina kuluttajien ruokavalintoihin ja ruokavalioon. Lisäksi ruoan valintaan liittyviä motiiveja, kuten hintaa, makua, helppoutta ja terveyttä, pidetään käytännöllisempinä motiiveina, jotka vaikuttavat kuluttajien ostopäätöksiin ja ruokavalintoihin. Ammattiurheilijoiden luontaiset sisäiset motivaatiot, joihin kuuluu mm. pyrkimys maksimoida urheilullinen suorituskyky, vaikuttavat urheilijoiden ruokavalintoihin, riippuen urheilijan tavoitteista ja kilpailukauden ajankohdasta. Sisäisten motivaatioiden lisäksi myös ulkoiset motivaatiot vaikuttavat urheilijoiden ruokavalintoihin tietyissä tilanteissa. Ulkoiset motivaatiot eivät kuitenkaan perustu urheilijan omaan motivaatioon, ja ne ovat lähtöisin esimerkiksi ystävien, perheen tai valmentajien olemassaolosta, painostuksesta, ohjeistuksesta, tiedonannosta tai tuesta. Tutkimus tehtiin laadullisena tutkimuksena puolistrukturoituina haastatteluina, ja tutkimukseen osallistui eri lajien ammattiurheilijoita. Tutkimustulokset viittaavat siihen, että urheilijat ovat huolissaan terveys- ja ympäristötekijöistä, joihin heidän ruokavalionsa ja kulutustottumuksensa vaikuttavat. Tärkeimmät ruoanvalintamotiivit, jotka heijastavat heidän ruokavalintojaan, ovat maku, hinta ja helppous. Erityisesti helppous on vaikuttava motiivi urheilijoille, mikä saa heidät usein suosimaan helposti ja nopeasti valmistettavia ruokia, jotka sopivat heidän kiireiseen harjoittelu- ja kilpailuohjelmaansa. Urheilijat olisivat motivoituneita tekemään kestävämpiä ruokavalintoja, jos se edistäisi positiivisesti myös heidän urheilullista suorituskykyään, ja jos heidän ystävänsä tai kumppaninsa söisivät vastaavia ruokia. Yksi tärkeimmistä tutkimustuloksista oli tiedon puute ruoan kestävyysasioista, mikä on usein este sellaisten ruokavalintojen tekemiselle, jotka tukevat niin maapallon kestävyyttä, kuin urheilullista suorituskykyä.
Keywords: sustainable food choice, plant-based, personal values, food choice motive, intrinsic motivation, extrinsic motivation